Modulation of immune responses to liposomal vaccines by intrastructural help - Damm, Dominik; Suleiman, Ehsan; Wagner, Jannik; Klessing, Stephan; Pfister, Felix; Elsayed, Hassan; Walkenfort, Bernd; Stobrawe, Jule; Mayer, Julia; Lehner, Elisabeth; Müller-Schmucker, Sandra; Hasenberg, Mike; et al. (European Journal of Pharmaceutics and Biopharmaceutics, 2023)
The encapsulation of HIV-unrelated T helper peptides into liposomal vaccines presenting trimers of the HIV-1 envelope glycoprotein (Env) on the surface (T helper liposomes) may recruit heterologous T cells to provide help for Env-specific B cells. This mechanism called intrastructural help can modulate the HIV-specific humoral immune response. In this study, we used cationic T helper liposomes to induce intrastructural help effects in a small animal model. The liposomes were functionalized with Env trimers by a tag-free approach designed to enable a simplified GMP production. The pre-fusion conformation of the conjugated Env trimers was verified by immunogold electron microscopy (EM) imaging and flow cytometry. The liposomes induced strong activation of Env-specific B cells in vitro. In comparison to previously established anionic liposomes, cationic T helper liposomes were superior in CD4+ T cell activation after uptake by dendritic cells. Moreover, the T helper liposomes were able to target Env-specific B cells in secondary lymphoid organs after intramuscular injection. We also observed efficient T helper cell activation and proliferation in co-cultures with Env-specific B cells in the presence of cationic T helper liposomes. Mouse immunization experiments with cationic T helper liposomes further revealed a modulation of the Env-specific IgG subtype distribution and enhancement of the longevity of antibody responses by ovalbumin- and Hepatitis B (HBV)-specific T cell help. Thus, clinical evaluation of the concept of intrastructural help seems warranted.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Env trimer; Functionalization; HIV vaccine; IgG subtype; Intrastructural help; Nanoparticle; Peptide encapsulation; T helper liposomes